THE ROLE OF WATER IN THE PETROGENESIS OF MARIANA TROUGH MAGMAS - Stolper E.; Newman S. (My University, 1994)
Most variations in composition among primitive basalts from the Mariana back-arc trough can be explained by melting mixtures of an NMORB-type mantle source and an H2O-rich component, provided the degree of melting is positively and approximately linearly correlated with the proportion of the H2O-rich component in the mixture. We conclude that the degrees of melting by which Mariana trough magmas are generated increase from magmas similar to NMORB, through more H2O-enriched basalts, to ‘arc-like’ basalts, and that this increase is due to the lowering of the solidus of mantle peridotite that accompanies addition of the H2O-rich component is likely to be ultimately derived from fluid from a subducting slab, but we propose that by the time fluids reach the source regions of Mariana trough basalts, they have interacted with sufficient mantle material that for all but the most incompatible of elements (with respect to fluid-mantle interaction), they are in equilibrium with the mantle. In contrast, fluids added to the source regions of Mariana island-arc magmas have typically interacted with less mantle and thus retain the signature of slab-derived fluids to varying degrees for all but the most compatible elements. Primitive Mariana arc basalts can be generated by melting mixtures of such incompletely exchanged slab-derived fluids and sources similar to NMORB-type mantle sources, but the degrees of melting are typically higher than those of Mariana trough NMORB and the sources have been variably depleted relative to the back-arc sources by previous melt extraction. This depletion may be related to earlier extraction of back-arc basin magmas or may evolve by repeated fluxing of the sources as fluid is continually added to them in the regions of arc magma generation. If fluid with partitioning behavior relative to the solid mantle similar to that deduced for the H2O-rich component involved in the generation of Mariana trough basalts were extracted from primitive mantle, the residual mantle would have many of the minor and trace element characteristics of typical oceanic upper mantle; primitive mantle enriched in such fluid would be a satisfactory source for the continental crust in terms of its trace and minor element chemical composition.